The construction of children's cultural identity in the digital era: an analysis of the family's role in Ternate City - Umar, Sitirahia Hi; Abbas, Irwan; Wibowo, Irham; Mas’ud, Fadil (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2025)
This study examines the role of the family in shaping children’s cultural identity in the digital era, with a focus on communities in Ternate City. Amid rapid technological advancement and the pervasive influence of global culture through digital media, families face significant challenges in transmitting local cultural values to younger generations. The urgency of this issue lies in the growing threat of cultural homogenization and the potential erosion of local traditions if not actively preserved. Using a qualitative descriptive method, this study investigates how families act as digital cultural curators by integrating cultural literacy and digital literacy in everyday life. Data were collected through interviews, observations, and documentation to capture the ways in which parents and elders instill cultural values while guiding children’s engagement with digital platforms. The findings indicate that families play a central role in constructing children’s cultural awareness through practices such as storytelling, participation in local traditions, and the supervised use of digital media. These strategies not only maintain the continuity of cultural heritage but also enhance children’s critical skills in navigating digital spaces. The novelty of this research lies in positioning the family as a key agent of cultural preservation in the digital landscape. By framing the family as digital cultural curators, this study contributes a conceptual model for strengthening children’s cultural identity amid the pressures of globalization and digital transformation.